Establishment of Sakinah Aisyiyah Center (BSA) to Prevent Stunting - Rohmah, Fayakun Nur; Faidati, Nur (Journal of Community Services and Engagement: Voice of Community (VOC), 2023)
Data from the Sleman Health Office showed that the prevalence of stunting in the Gamping I Health Center was 9.02% and 9.76% in the Gamping II Health Center. The number of cases of stunting in Nogotirto Village for 2021 data has reached 73 cases. Most stunting incidents are caused by the rejection of stunting under five due to a lack of understanding of stunting, poor parenting factors, and feeding practices for infants and toddlers. For this reason, there is a need for a community-based stunting prevention movement, as stated in the 2020-2024 policy directions contained in the Indonesia SDGs Roadmap Towards 2030. Solution: Formation of Balai Sakinah 'Aisyiyah (BSA), formation of cadres, training of cadres, and provision of reading corners and educational media. Method: establishing BSA, increasing cadres’ knowledge about stunting, IMD, exclusive breastfeeding, lactation management, and provision of MP-ASI and providing books and reading corner facilities for cadres; Provision of Cadre Education Media in preventing stunting. Results: the formation of 28 BSA cadres, there was an increase in cadre knowledge of> 25%, available reading corners, and educational media.